PENCAPAIAN KETUNTASAN BELAJAR DENGAN MODUL PADA MATA PELAJARAN AKUNTANSI PERUSAHAAN JASA - Nur Lailatul Q., (Pendidikan Ekonomi, 2011)
The objective of the study was to examine the use of instructional module of service firm accounting to increase the learning mastery of eleventh graders of SMA Wachid Hasyim 2 Taman. The classroom action research consisted of two cycles. The data collection techniques were observation, test, and documentation. The data were then analyzed through cyclical reflections. The result of the study showed that through the use of instructional module, the students and teachers instructional activities improved. Additionally, all students in the designated class achieved the learning mastery.